Diferentes métodos e tempos de conservação de amostras de leite cru para determinação da composição físico-química e qualidade microbiológica - Wentz, Andréia Garcia (2016)
The present study aimed to compare three methods of conservation (no added preservative, azidiol and bronopol), conservation of raw milk for total bacteria count analysis (TBC) for the standard counting method plating, chemical composition (fat, protein, lactose, total solids and fat solids), pH and freezing of milk. The research also aimed to study the influence of the storage period (days), temperature (cooled and uncooled) and the initial microbiological quality of raw milk samples. It was used a randomized block design with factorial arrangement of 3 (methods) x 2 (temperature) x 5 (times). The TBC was influenced by the preservative, since after seven days of storage the sample without preservative had greater TBC. In the unrefrigerated samples with bronopol there was a gradual reduction of TBC. It was observed that the samples preserved with azidiol, regardless of storage temperature, TBC reduced over time. The temperature affected the fat content (P <0.001). The protein, lactose, solids and milk medium density were influenced by the type of preservative and storage days (P <0.001). The pH was influenced by the type of preservative and the storage days (P <0.001). For TBC analysis, the use of azidiol, independent of refrigeration or storage, is the most appropriate method to maintain the original characteristics of the product. From the first day of storage of the samples, there was an increase of the average levels of protein, lactose and degreased solids in relation to the quantified on the collection day. On the other hand, the TBC was changed isolated by the initial TBC, storage temperature and storage days (P <0.001). There was an increase of TBC according to the days of storage, since until the first day of storage values increased already from the second day of storage TBC started to reduce. In fat content, there was only initial TBC effect and storage temperature (P <0.001). In the protein percentage there was the effect of days of storage, the protein increased until the first day of storage, where it stabilized until 7 days of storage. Lactose was amended by initial TBC and the storage days (P <0.001), lactose increased until the first day of storage, which stabilized until the seventh day. The total solids (TS) content was amended by initial TBC, temperature and storage days (P <0.001), samples with high TBC showed higher initial TS levels. The SD content was changed only by the initial TBC and the storage days (P <0.001). The pH was amended by initial TBC, temperature and days of storage. For TBC analysis, using azidiol preservative is dependent on the use of refrigeration during storage to maintain more stable microbiological characteristics over seven days of storage. For analysis of physical and chemical composition, from the first day of sample storage, there was an increase of protein, lactose and fat solids of milk, compared to levels observed when quantified in the same day of collection of milk